A vida após dez anos do acolhimento institucional: a processualidade dos afetos e vínculos - Bento, Rilma (2019)
This thesis discusses foster care and leaving the institution by analyzing what happened in the life of a young person ten years after leaving foster care upon reaching adulthood. The subject of the research was in institutional foster care and was attended by the researcher in the program “Family Replacement” in the years 2006 and 2007, in a municipality of the ABCD region of São Paulo. I sought to identify how the young person reorganized a decade after leaving foster care, by judicial decision, to date, analyzing the quality of the attachments in his procedure, which he had built with people in the family and institutional context, during that period. The data collection was conducted qualitatively and longitudinally, through the retrospective method, which uses the life narratives or biographical interview to reconstruct sequences of events in the life of individuals. The following procedures were used: bibliographic and documentary research, including laws, ordinances, research, and official documents of the judiciary, analysis of the subject’s medical records, and semi-structured interviews with the subject and with people in his family, in an attempt to encompass the totality of his life. The study is guided by the theory of socio-historical psychology, whose main theorist is Vygotsky and, in Brazil, Lane, as appropriated by NEXIN and its coordinator, Sawaia. The theoretical framework also included, respecting the epistemological differences, Winnicott’s concepts, which deal with the relationship between emotional development and the environment. Using the investigation method proposed by Vygotsky, we searched for units of meaning, common and individual. The results indicate that the type of follow-up the subject and his family received, before, during, and after leaving the foster institution, by the judiciary and public services, were insufficient to guarantee the principles of the right to family and community living, in a satisfactory way. He lacked preparation for life after leaving the institution, and the adolescent had to deal with the lack of care and protection. There was no professional preparation. Evidence shows that his professional trajectory was left to chance, as well as the difficulty of the subject to establish bonds, because the relations are easily disrupted and do not sustain for a long time, with prevalent feeling that people give up on him. He tries to maintain the connection with the territorial space to which he has already felt the he belonged, being guided by the search to create and revive affective family and institutional bonds. The family is not always the place of affective exchanges that empower, protect, and accept of its members. Thus, we question the intervention and pressure of the State to prioritize the coexistence with family members, even when it does not have availability to produce such a feat. This study prompts the need to discover ways that may instigate impediments to new psychosocial practices directed at children and adolescents during and after institutional foster care